Milk Proteins - From Structure to Biological Properties and Health Aspects 2016
DOI: 10.5772/64416
|View full text |Cite
|
Sign up to set email alerts
|

An Important Milk Enzyme: Lactoperoxidase

Abstract: It has been acknowledged since ancient times that milk and dairy products have a vital role in nutrition and contribute considerably to human health. Because of its content, Because of its content, it has many important effects on the life that include immunoglobulins, enzymes, hormones, growth factors, antibacterial agents, fat acids, vitamins, and minerals. Approximately indigenous enzymes have been reported in normal bovine milk, including lactoperoxidase. Lactoperoxidase LPO is a natural constituent of mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 57 publications
0
10
0
1
Order By: Relevance
“…On the other hand, the natural antioxidants of sesame meal didn’t affect negatively the LPO activity in goats’ milk ( Table 3 ). This is very important because this enzyme has anti-microbial effects which erase the harmful effects of microorganisms in the animals’ mammary glands [ 43 ]. Moreover, the LPO system has a pivotal role in dairy industry in the preservation of raw milk [ 44 ], cheese [ 45 ], and yogurt [ 46 ], and can be used to extend the shelf-life of pasteurized milk as well [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the natural antioxidants of sesame meal didn’t affect negatively the LPO activity in goats’ milk ( Table 3 ). This is very important because this enzyme has anti-microbial effects which erase the harmful effects of microorganisms in the animals’ mammary glands [ 43 ]. Moreover, the LPO system has a pivotal role in dairy industry in the preservation of raw milk [ 44 ], cheese [ 45 ], and yogurt [ 46 ], and can be used to extend the shelf-life of pasteurized milk as well [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 ] Compounds with antioxidant effect on metabolism inactivate oxidants as reductants. [ 29,38 ] Free Fe 3+ is added to the test medium and a Prussian blue solution is formed. Fe 4 [Fe(CN) 6 ] 3 formed as a result of the reaction gives strong absorbance at 700 nm.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Lorenzen et al (2010) found averages of 2,015, 2,796 and 5,190 U/L LPO in raw milk from cows, sheep and goats, respectively. LPO is an oxidoreductase, with its main function in milk being to oxidise molecules in the presence of hydrogen peroxide, providing an antimicrobial function (Koksal et al, 2016).…”
Section: Lactoperoxidase (Lpo)mentioning
confidence: 99%